Isolation and ars Detoxification of Arsenite-Oxidizing Bacteria from Abandoned Arsenic-Contaminated Mines - Chang, Jin-Soo; Yoon, In-Ho; Kim, Kyoung-Woong (Journal of microbiology and biotechnology, 2007)
The ecosystems of certain abandoned mines contain arsenic-resistant bacteria capable of performing detoxification when an ars gene is present in the bacterial genome. The ars gene has already been isolated from Pseudomonas putida and identified as a member of the membrane transport regulatory deoxyribonucleic acid family. The arsenite-oxidizing bacterial strains isolated in the present study were found to grow in the presence of 66.7 mM sodium arsenate($V;\;Na_2HAsO_4{·}7H_2O$), yet experienced inhibited growth when the sodium arsenite($III;\;NaAsO_2$) concentration was higher than 26 mM. Batch experiment results showed that Pseudomonas putida strain OS-5 completely oxidized 1 mM of As(III) to As(V) within 35 h. An arsB gene encoding a membrane transport regulatory protein was observed in arsenite-oxidizing Pseudomonas putida strain OS-5, whereas arsB, arsH, and arrA were detected in strain OS-19, arsD and arsB were isolated from strain RW-18, and arsR, arsD, and arsB were found in E. coli strain OS-80. The leader gene of arsR, -arsD, was observed in a weak acid position. Thus, for bacteria exposed to weak acidity, the ars system may cause changes to the ecosystems of As-contaminated mines. Accordingly, the present results suggest that arsR, arsD, arsAB, arsA, arsB, arsC, arsH, arrA, arrB, aoxA, aoxB, aoxC, aoxD, aroA, and aroB may be useful for arsenite-oxidizing bacteria in abandoned arsenic-contaminated mines.